MAKNA YURIDIS STATUS HUKUM HAK WARIS ANAK HASIL DARI PERKAWINAN YANG TIDAK DICATATKAN MENURUT KOMPILASI HUKUM ISLAM - Nama, Zidna (Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract The aim of this jurnalis to determine the meaning of judicial and juridicalimplications of the legal status of the inheritance rights of a child who is born from the unregistered marriage accordingto KHI. The method used in this jurnal is a normative study by using conceptual approach of legislation and then assisted with legal materials that will be outlined, described, and analyzed its relationship between one and another.A child can become an heir according to Islam is based on family lineage that come fromthe existence of a valid marriage according to the religion. According to KHI, the validity of a marriage not only has to fulfill the requirements of valid marriage but also has to fulfill the registration of the marriage. If not, it will cause a marriage that has no legal force, and it will impact to the inheritance relationship that is not going to have a legal force as well. The implication of the juridical status of the inheritance rights of children from an unregistered marriage is there is no protection of law and justice, due to a loss of status for the childs inheritance rights. Key words: inheritance rights, child who is born from the unregistered marriage, compilation of islamic law. Â  Abstrak Jurnal ini bertujuan untukÂ  mengetahui makna yuridis dan implikasi yuridis status hukum hak waris anak yang dilahirkan dari perkawinan yang tidak dicatatkan menurut KHI. Metode yang digunakan dalam jurnal ini adalah penelitian yuridis normatif, dengan menggunakan pendekatan perundang-undangan yang bersifat konseptual. Kemudian dibantu dengan bahan-bahan hukum yang akan diuraikan, dideskripsikan, dan dianalisis keterkaitan satu sama lain. Seorang anak dapat menjadi ahli waris menurut agama Islam selalu berdasar pada adanyahubungan nasab yang ditimbulkan dari adanya perkawinan yang sah menurut agama,tetapi menurut KHI untuk sahya suatu perkawinan selain harus memenuhi rukun dan syarat perkawinan juga harus memenuhi syarat pencatatan,yang jika tidak dilakukan akan berakibat perkawinan tersebut tidak mempunyai kekuatan hukum. Implikasi yuridis terhadap status hak waris anak dari perkawinan yang tidak dicatatkan yaitu belumterwujudnya perlindungan hukum dan keadilan, karena terhapusnya status hak waris bagi anak tersebut. Kata kunci: hak waris, anak hasil dari perkawinan yang tidak dicatatkan, kompilasi hukum islam. Â